2018
DOI: 10.1002/asia.201800953
|View full text |Cite
|
Sign up to set email alerts
|

N‐Formylation of Amines with CO2 and H2 by Using NHC–Iridium Coordination Assemblies as Solid Molecular Catalysts

Abstract: One of the NHC-iridium coordination assemblies containing 1,5-cyclooctadiene (COD) and iodide ion has been demonstrated as robust, efficient, recyclable solid molecular catalyst for N-formylation of diverse primary and secondary amines with CO and H under mild reaction conditions. Remarkably, in the case of N,N-dimethylformamide production, even at 0.1 mol % catalyst loading under solvent-free conditions, the solid catalyst can be readily recovered by simply filtration and reused more than 10 runs without noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 56 publications
1
20
0
1
Order By: Relevance
“…As shown in Figure 3 a, in the presence of 0.002 mol % catalyst loading under a CO 2 /H 2 partial pressure of 40/40 atm at 120 °C for 24 hours, POMP‐NHC‐Ir 2 a – h exhibited much higher catalytic activity than their homogeneous precursor bis‐NHC‐Ir complex 1 . 1 H NMR and GC analyses of the reaction mixtures revealed that water was the only byproduct, in consistency with the previous reports [9, 11a] . For comparison, other known viable homogeneous catalysts 4 – 6 for the N‐formylation were also tested under the optimized reaction conditions, and much lower yields were attained (Figure 3 a).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in Figure 3 a, in the presence of 0.002 mol % catalyst loading under a CO 2 /H 2 partial pressure of 40/40 atm at 120 °C for 24 hours, POMP‐NHC‐Ir 2 a – h exhibited much higher catalytic activity than their homogeneous precursor bis‐NHC‐Ir complex 1 . 1 H NMR and GC analyses of the reaction mixtures revealed that water was the only byproduct, in consistency with the previous reports [9, 11a] . For comparison, other known viable homogeneous catalysts 4 – 6 for the N‐formylation were also tested under the optimized reaction conditions, and much lower yields were attained (Figure 3 a).…”
Section: Resultssupporting
confidence: 87%
“…Other commercially available catalysts, like Vaska's catalyst 6 , resulted in trace amount of DMF. In the case of our previously reported linear nonporous self‐supported NHC‐Ir coordination polymer 3 a with a BET surface area of 8 m 2 g −1 , [11a] only 36 % yield was achieved at such low catalyst loading. All these outcomes indicated that the preserved chemical environment around the iridium center, large specific surface area, hierarchical porous structure of POMP‐NHC‐Ir were all necessary to achieve satisfactory outcomes in the challenging catalytic N‐formylation reaction with CO 2 and H 2 .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Later, Tu and co-workers explored a series of NHC-Ir coordination assemblies as solid molecular catalysts for N-formylation of diverse amines. 63 Moderate yield of DMF was attained, even at 0.1 mol% catalyst loading, and the solid catalyst could be reused more than 10 runs.…”
Section: Xiao-feng Wumentioning
confidence: 98%
“…Moreover, recycling of the catalyst was also demonstrated for up to 12 cycles for the production of N, N‐dimethylformamide without significant loss of activity. Tu has recently reported a solid molecular catalyst based on the iridium‐NHC coordination assembly ( Ir‐3 , Figure 6) for the N‐formylation of a variety of amines using CO 2 and H 2 [90] . A solid molecular catalyst allowed easy recovery of the catalyst by a simple filtration process that could be used more than 10 times without loss of activity for the production of DMF in solvent‐free conditions.…”
Section: Carbon Dioxidementioning
confidence: 99%